2009
DOI: 10.1299/jamdsm.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Additional Electrical Current on Machinability of BN Free-Machining Steel in Turning

Abstract: It is widely known that the electromotive force generated at the interface between the cutting tool and work material, during a metal cutting process, influences the cutting mechanism. Previously published papers describe the influence of the passage of electric current through the contact zone between cutting tool and work material, on tool life in cutting several work materials. However, few papers deal with the influence of this electric current on the behavior of a deposited layer called "belag", observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In recent years, the possibility of adding BN to improve the machinability of steel was explored (Tanaka et al, 2007;Tanaka et al, 2009). The influences of steel composition and tool material on the machinability have been investigated and confirmed that BN inclusions could improve the machinability of steel significantly.…”
Section: Introductionmentioning
confidence: 95%
“…In recent years, the possibility of adding BN to improve the machinability of steel was explored (Tanaka et al, 2007;Tanaka et al, 2009). The influences of steel composition and tool material on the machinability have been investigated and confirmed that BN inclusions could improve the machinability of steel significantly.…”
Section: Introductionmentioning
confidence: 95%
“…[8] are shown in Table IV. [23,24] Combined with the data in Table IV Equation [10] confirms that in the liquid region and the mushy region, DG>0.…”
Section: A Thermodynamic Condition Of Bn Precipitationmentioning
confidence: 99%
“…Boron nitride, also called 'white graphite', has a hexagonal lattice and behaves similar to graphite, i.e. acts as a lubricant in steel machining processes [11][12][13][14]. According to available literature, boron nitride inclusions do not affect anisotropy of mechanical properties, increase strength, have positive effect on machinability and cause no environmental problems.…”
Section: Introductionmentioning
confidence: 99%